Предмет: Математика,
автор: hakop27
Найдите значение выражения
Приложения:

Ответы
Автор ответа:
1
Ответ:
64
Пошаговое объяснение:
(1/8 + 1/4)^(-2) ÷ ((корень из 5 + 2)^2 - 4 × корень из 5)^(-1) = (1/8 + 2/8)^(-2) ÷ (5 + 4 × корень из 5 + 4 - 4 × корень из 5)^(-1) = (3/8)^(-2) ÷ (5 + 4)^(-1) = ( 1 / (3/8) )^2 ÷ 9^(-1) = (8/3)^2 ÷ 1/9 = 8/3 × 8/3 × 9 = (8×8×9) / (3×3) = 8×8 = 64
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Другие предметы,
автор: Elli5
Предмет: Математика,
автор: Настюшка240
Предмет: Физика,
автор: Chucanova280
Предмет: Математика,
автор: никита3393